2011
DOI: 10.3109/1354750x.2010.547948
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic profile of excessive body weight

Abstract: The purpose of this paper is to identify immunologic hallmarks of excessive bodyweight. The analysis is based on 176 adults (106 women, 70 men) who participated in a nested case-control study in Italy. All participants were healthy at the time of blood collection and aged between 36 and 75 years. We employed multivariate analysis of variance and a nonparametric Bayesian additive regression tree approach along with a receiver operating characteristic (ROC) curve analysis to determine the immunologic signature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 101 publications
4
39
0
Order By: Relevance
“…For a broader investigation of biomarkers, some working groups applied multiplex cytokine measurements in the blood samples of MetS patients and reported a range of cytokine concentrations comparable to those measured in our study (Schipper et al, 2010;Bremer et al, 2011;Sharabiani et al, 2011;Surendar et al, 2011;Tisato et al, 2013). We identified IL-6 and IL-10 to be significantly elevated in MetS patients.…”
Section: Discussionmentioning
confidence: 73%
“…For a broader investigation of biomarkers, some working groups applied multiplex cytokine measurements in the blood samples of MetS patients and reported a range of cytokine concentrations comparable to those measured in our study (Schipper et al, 2010;Bremer et al, 2011;Sharabiani et al, 2011;Surendar et al, 2011;Tisato et al, 2013). We identified IL-6 and IL-10 to be significantly elevated in MetS patients.…”
Section: Discussionmentioning
confidence: 73%
“…Results of our study within the EPIC-Italy (Taghavi Azar Sharabiani et al 2011) suggested that IL8, IL10, IFN-, and IP10 are related to obesity (Body mass index; BMI). Among these predictors, IP10 had the highest prognostic value for obesity.…”
Section: Obesitymentioning
confidence: 99%
“…In the two studies described previously (Saberi Hosnijeh, Krop, Scoccianti, et al 2010;Taghavi Azar Sharabiani et al 2011), no overlap was observed between marker levels of obesity and NHL (as based on the original concept of ''meet in the middle'' approach). However, a potential role of obesity in lymphomagenesis cannot be excluded because, on one hand, several studies showed that obesity is a lowgrade chronic inflammatory state and, on the other hand, a chronic inflammatory condition has been linked to NHL risk in previous epidemiological studies (Smedby et al 2011).…”
Section: Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data indicate that macrophages in obese adipose tissue are major source of most mediators. Therefore weight loss is associated with a reduction in the macrophage infiltration of adipose tissue and an improvement of the inflammatory profile [39][40][41][42][43][44][45].…”
Section: Effects Of Inflammatory Mediators On Glucose Metabolismmentioning
confidence: 99%